2011
DOI: 10.1098/rstb.2010.0411
|View full text |Cite
|
Sign up to set email alerts
|

Integrating natural and social science perspectives on plant disease risk, management and policy formulation

Abstract: Plant diseases threaten both food security and the botanical diversity of natural ecosystems. Substantial research effort is focused on pathogen detection and control, with detailed risk management available for many plant diseases. Risk can be assessed using analytical techniques that account for disease pressure both spatially and temporally. We suggest that such technical assessments of disease risk may not provide an adequate guide to the strategies undertaken by growers and government to manage plant dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 64 publications
4
84
0
Order By: Relevance
“…Thus, plant health strategies need to shift from a technocratic or decisionistic model towards a transparent and inclusive governance model. Observing the decisionistic model applied to P. ramorum management in the UK, national consultative meetings were organized, as well as regional ones in most infected areas, and communication between government and stakeholder groups was seen as a critical step for the successful implementation of policy outcomes [8]. The result of meetings and debates was that ministers concluded that more needed to be done to contain and eradicate P. ramorum.…”
Section: Cvcmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, plant health strategies need to shift from a technocratic or decisionistic model towards a transparent and inclusive governance model. Observing the decisionistic model applied to P. ramorum management in the UK, national consultative meetings were organized, as well as regional ones in most infected areas, and communication between government and stakeholder groups was seen as a critical step for the successful implementation of policy outcomes [8]. The result of meetings and debates was that ministers concluded that more needed to be done to contain and eradicate P. ramorum.…”
Section: Cvcmentioning
confidence: 99%
“…A further step towards a broader involvement of plant health professionals and researchers was the establishment of a task force in late 2015, while public debates at national, regional, and local levels were countless since the disease outbreak, even if not always formally organized. However, the case of P. ramorum in the UK underlines how the value of consultation and meeting depended on the diversity of organizations attending, because debates were not always able to attract key organizations or influencing groups that would lead to a broader and effective discussion with significant outcomes [8]. In Apulia, outcomes of consultations were numerous, but as of September 2016, the plant health policy is substantially linked to the European Directive, and the perception of a technocratic approach seems difficult to eradicate from the grower community as a whole.…”
Section: Cvcmentioning
confidence: 99%
See 2 more Smart Citations
“…Tighter European Union rules on the use of chemical pesticides are likely to increase the role of genetic diversity in order to keep many pathogens of crops under control [7]. Nonetheless, a more environmentally friendly management of diseases is just one of the reasons to preserve genetic diversity.…”
Section: New Approaches and Tools To Study And Manage Genetic Resourcesmentioning
confidence: 99%